Capturing protein droplets: label-free visualization and detection of protein liquid–liquid phase separation with an aggregation-induced emission fluorogen. Issue 31 (19th March 2021) - Liang, Chu-Qiao; Wang, Lin; Luo, Yun-Yi; Li, Qian-Qian; Li, Yan-Mei
Abstract : Methods for visualizing label-free protein liquid–liquid phase separation and measuring the viscosity of the protein condensed phase are developed. Abstract : We developed a new method for protein droplet visualization by means of a droplet probe (DroProbe) based on an aggregation-induced emission (AIE) fluorogen. A simple method for viscosity comparison of the protein condensed phase based on the lifetime of the DroProbe was also developed.